Infant vaccination timing: Beyond traditional coverage metrics for maximizing impact of vaccine programs, an example from southern Nepal. Issue 7 (10th February 2016) - Hughes, Michelle M.; Katz, Joanne; Englund, Janet A.; Khatry, Subarna K.; Shrestha, Laxman; LeClerq, Steven C.; Steinhoff, Mark; Tielsch, James M.
Highlights: We prospectively examined, via weekly recall, the timing of EPI immunizations in infants less than 6 months in rural Nepal. The majority of infants less than 6 months received immunizations on a delayed schedule. National immunization coverage estimates do not capture delay in the first 6 months of life. Abstract: Background: Immunization programs currently measure coverage by assessing the proportion of children 12–24 months who have been immunized but this does not address the important question of when the scheduled vaccines were administered. Data capturing the timing of vaccination in first 6 months, when severe disease is most likely to occur, are limited. Objective: To estimate the time to Bacillus Calmette–Guérin (BCG) (recommended at birth), diphtheria-tetanus-pertussis-H, influenza b-hepatitis B (DTP-Hib-HepB), and oral polio vaccine (OPV) (recommended at 6, 10, and 14 weeks) vaccinations and risk factors for vaccination delay in infants <6 months of age in a district in southern Nepal where traditional coverage metrics are high. Design/methods: Infants enrolled in a randomized controlled trial of maternal influenza vaccination were visited weekly at home from birth through age 6 months to ascertain if any vaccinations had been given in the prior week. Infant, maternal, and household characteristics were recorded. BCG, DTP-Hib-HepB, and OPV vaccination coverage at 4 and 6 months was estimated. Time to vaccination was estimated through Kaplan–Meier curves; Cox-proportional hazards models were used to examine risk factors for delay for the first vaccine. Results: The median age of BCG, first OPV and DTP-Hib-HepB receipt was 22, 21, and 18 weeks, respectively. Almost half of infants received no BCG by age 6 months. Only 8% and 7% of infants had received three doses of OPV and DTP-Hib-HepB, respectively, by age 6 months. Conclusion: A significant delay in receipt of infant vaccines was found in a prospective, population-based, cohort in southern Nepal despite traditional coverage metrics being high. Immunization programs should consider measuring time to receipt relative to the official schedule in order to maximize benefits for disease control and child health.